Apomorphine therapy: alternative initiation for patients with complex Parkinson's disease presentation. (2nd December 2019) - Mills, Jane
ABSTRACT: The apomorphine challenge test can be a distressing experience for some patients and, if they are not experienced, a discouraging option for some healthcare professionals (HCPs). The test is repeated exposure to bolus-dose injection of the medication to assess response and patient-specific dose before embarking on apomorphine therapy. Recent changes in prescribing of the anti-emetic domperidone (limited use because of QT prolongation), a drug which is a prerequisite for most patients embarking on therapy, has also added a possible complication. While recognising the value of the apomorphine challenge test, the author suggests an alternative approach of establishing apomorphine by subcutaneous infusion pump (SCAI) without the challenge test. This approach makes it more 'user friendly' for people with complex Parkinson's disease (PwPd) and their HCPs, and can eliminate the need for preloading with domperidone or other anti-emetic (if one is available in the country of practice). It is a viable option in acute situations, such as nil by mouth, surgery and oral dopamine agonist withdrawal, because of the associated harmful impulsive behaviour. Starting immediately with SCAI without the challenge test has proven both helpful and beneficial in clinical practice, especially in PwPd who have potential to abuse the intermittent injection, have complicated regimens and are vulnerable to drug-induced adverse effects. Some patients only need nocturnal infusions; injections during the night are difficult to administer and miss the objective of better sleep. Facilitating the process of initiation with the SCAI could improve uptake of this underused treatment through easier use and positive experience, and overcome the need for short- and longer-term domperidone use.